THE EFFECT OF CONCEPTION OF INTERNET USAGE AND SMES’ ACTIVITIES ON ORGANIZATIONAL PERFORMANCE AMONG TOURISM ENTERPRISES IN MALAYSIA - Sharifonnasabia, Fatemeh; Raj, Ram Gopal; Marsukia, Mohd Zuhdi (Malaysian Journal of Computer Science, 2018)
Small and Medium Enterprises (SMEs) are the mainstays of economic development and advancement in numerous countries. SMEs add to monetary advancement in Malaysia by temperance of their utter numbers, expanded share of business and total national output. Innovation reception and Internet utilization development in Malaysian SMEs have enhanced the execution and primary concern of SMEs and information technology (IT) has turned out to be instrumental to the advancement and thriving of different areas. This study assesses the impact of view of Internet utilization, SMEs’ action and size on authoritative execution in this industry. Seventy-seven, randomly-identified SME organizations with the tourism business were arbitrarily chosen from Kuala Lumpur and Selangor, Malaysia. The information was gathered by means of a self-administrated poll from tourism organizations in these two zones. The information was dissected in view of the Structural Equation Modeling (SEM) utilizing SMART-Partial Least Squares (PLS). The outcomes uncovered that the observation level of Internet utilization and SME movement surpassed the direct level. The SEM discoveries likewise demonstrated that the acknowledgment of Internet use had a huge, constructive outcome on tourism authoritative execution in Malaysia.